Comparison of Treatments for Nonmetastatic Castration-Resistant Prostate Cancer: Matching-Adjusted Indirect Comparison and Network Meta-Analysis. (8th April 2021) - Wang, Lin; Paller, Channing; Hong, Hwanhee; Rosman, Lori; De Felice, Anthony; Brawley, Otis; Alexander, G Caleb
Abstract: Background: For nonmetastatic castration-resistant prostate cancer (nmCRPC), 3 drugs under patent protection—apalutamide, enzalutamide, and darolutamide—were approved based on randomized, placebo-controlled trials; 1 drug with generic availability, abiraterone acetate, showed efficacy in a single-arm trial and is commonly prescribed. Lacking head-to-head trials, the optimal treatment for nmCRPC is unknown, despite widely varied treatment costs. We compared the efficacy and safety of nmCRPC treatments. Methods: We searched bibliographic databases, regulatory documents, and trial registries for nmCRPC trials. We included published results and, when available, original data. We performed matching-adjusted indirect comparison and network meta-analysis and compared treatments regarding metastasis-free survival, overall survival, and serious adverse events. Results: We analyzed 5 trials with 4360 participants. Compared with placebo, abiraterone acetate engendered the lowest hazard of metastasis and death (hazard ratio [HR] = 0.22, 95% credible interval [CrI] = 0.12–0.41), followed by apalutamide (HR = 0.28, 95% CrI = 0.23–0.34), enzalutamide (HR = 0.30, 95% CrI = 0.25–0.36), and darolutamide (HR = 0.41, 95% CrI = 0.34–0.49); darolutamide led to the lowest hazard of death (HR = 0.69, 95% CrI = 0.53–0.90), followed by enzalutamide (HR = 0.73, 95% CrI = 0.61–0.87) and apalutamide (HR = 0.75, 95% CrI = 0.59–0.95); darolutamide resulted in the lowest odds of serious adverse events (odds ratio [OR] = 1.32, 95% CrI = 1.02–1.70), followed by enzalutamide (OR =1.43, 95% CrI = 1.08–1.89), apalutamide (OR = 1.58, 95% CrI = 1.23–2.03), and abiraterone acetate (OR = 1.94, 95% CrI = 1.17–3.22). Conclusions: For nmCRPC, darolutamide offered optimal efficacy and safety among approved drugs, and abiraterone acetate may offer comparable metastasis-free survival benefit with cost savings from generic availability. Future research is needed to more fully examine the benefit of abiraterone acetate.